2019
DOI: 10.1038/s41598-019-46321-6
|View full text |Cite
|
Sign up to set email alerts
|

The rpl23 gene and pseudogene are hotspots of illegitimate recombination in barley chloroplast mutator seedlings

Abstract: Previously, through a TILLING (Targeting Induced Local Lesions in Genomes) approach applied on barley chloroplast mutator ( cpm ) seedlings a high frequency of polymorphisms in the rpl23 gene was detected. All the polymorphisms corresponded to five differences already known to exist in nature between the rpl23 gene located in the inverted repeats (IRs) and the rpl23 pseudogene located in the large single copy region (LS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The presence of short perfect or imperfect direct repeats in the borders of the four large indels identified in the plastome of cpm seedlings is in agreement with the hypothesis that they originated as a consequence of increased rates of illegitimate recombination between these short repeats. Previously, illegitimate recombination was also postulated as the cause of the high frequencies of polymorphisms observed in the rpl23 gene and pseudogene in cpm seedlings (Lencina et al, 2019). These observations together with the increased rates of substitutions and small indels in microsatellites previously observed in cpm seedlings (Landau et al, 2016) Figure 1.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The presence of short perfect or imperfect direct repeats in the borders of the four large indels identified in the plastome of cpm seedlings is in agreement with the hypothesis that they originated as a consequence of increased rates of illegitimate recombination between these short repeats. Previously, illegitimate recombination was also postulated as the cause of the high frequencies of polymorphisms observed in the rpl23 gene and pseudogene in cpm seedlings (Lencina et al, 2019). These observations together with the increased rates of substitutions and small indels in microsatellites previously observed in cpm seedlings (Landau et al, 2016) Figure 1.…”
Section: Discussionmentioning
confidence: 72%
“…The vast majority of those polymorphisms were due to substitutions and small indels (insertions/deletions) in microsatellites. However, a peculiar spectrum that included several combinations of five single nucleotide polymorphisms was observed in the rpl23 gene, which was later explained as arisen not from mutations, but from increased illegitimate recombination between the rpl23 gene and its pseudogene (Lencina et al, 2019). Besides the polymorphisms mentioned above, four large indels were found, which are the subject of analysis of the present work.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the grass plastome, the rpl23 gene is originally located in the IR region and encodes the functional ribosomal protein L23. Present studies have indicated that rpl23 has been non-reciprocally translocated to a region downstream from rbcL (Bowman et al, 1988;Ogihara et al, 1988;He et al, 2017;Lencina et al, 2019). A non-reciprocal translocation of the rpl23 gene occurred during the differentiation of Poaceae from its unknown ancestor (Katayama and Ogihara, 1996).…”
Section: Discussionmentioning
confidence: 83%
“…At least 61 different mutational events were detected; most of them were transitions and mono nucleotide indels [29]. This strategy also allowed the discovery of a high frequency of seedlings carrying different combinations of five polymorphisms, which already exist in nature, between the rpl23 gene and its pseudogene, which are postulated to originate in an increased rate of illegitimate recombination between these two loci [30]. All the results suggest that the failure of the cpm gene corresponds to a malfunction of a mismatch repair (MMR) gene involved in maintaining the stability of the plastome and that the cpm mutant constitutes an exceptional experimental material to obtain genetic variability in the otherwise highly conserved plastid genome.…”
Section: 4) Cptilling (Targeting Induced Local Lesions In Genomes): a High Throughput Screening Strategy For Isolation Of Plastome Mutantmentioning
confidence: 99%